The psychology of sales success : - Gschwandtner, Gerhard (McGraw-Hill, 2007)
This anthology examines the social construction of race, class, gender, and sexuality and the institutional bases for these relations. While other texts discuss various forms of stratification and the impact of these on members of marginalized groups, Ore provides a thorough discussion of how such systems of stratification are formed and perpetuated and how forms of stratification are interconnected. The anthology supplies sufficient pedagogical tools to aid the student in understanding how the material relates to her/his own life and how her/his own attitudes, actions, and perspectives may serve to perpetuate a stratified system